2022
DOI: 10.2478/auseb-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oil Price on Economic Growth in Middle-Income Oil-Importing Countries: A Non-Linear Panel ARDL Approach

Abstract: In this study, the impact of the crude oil price on economic growth is investigated in seven middle-income oil-importing countries in sub-Saharan Africa (SSA), namely Botswana, Kenya, Mauritania, Mauritius, Namibia, South Africa, and Zambia. The estimation is based on both linear and non-linear panel autoregressive distributive lag (panel ARDL) models. The real oil price is decomposed into negative oil price shock and positive oil price shock in order to examine the non-linear impact of oil price on economic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Likewise, Eyden et al (2019), Katircioglu et al (2015) find that the price of oil is negatively impacting the economic growth of OECD countries in general, including the oil exporters among them. In the same vein, Alkhateeb and Sultan (2019), Akinsola and Odhiambo (2020), Kriskkumar and Naseem (2019), Akhmad et al (2019) all find that, it is a negative relationship that exists between oil price changes and economic growth for different countries. Similarly, Moshiri (2015) indicated that different responses to oil price shock can be explained according to the individual country's differences in terms of institutional quality.…”
Section: Introductionmentioning
confidence: 91%
“…Likewise, Eyden et al (2019), Katircioglu et al (2015) find that the price of oil is negatively impacting the economic growth of OECD countries in general, including the oil exporters among them. In the same vein, Alkhateeb and Sultan (2019), Akinsola and Odhiambo (2020), Kriskkumar and Naseem (2019), Akhmad et al (2019) all find that, it is a negative relationship that exists between oil price changes and economic growth for different countries. Similarly, Moshiri (2015) indicated that different responses to oil price shock can be explained according to the individual country's differences in terms of institutional quality.…”
Section: Introductionmentioning
confidence: 91%
“…Despite the extensive literature on this topic (Lee et al , 1995; Rafiq et al , 2009; Soytas et al , 2009; Aguiar-Conraria and Soares, 2011; Tiwari, 2013, etc.) the relationship between oil price fluctuations and economic activity is complex and varies depending on the country’s level of oil dependence (Nasir et al , 2019; Akinsola and Odhiambo, 2020) and the causes of shocks (Wan and Kao, 2015). However, several theoretical explanations for this relationship have been proposed.…”
Section: Introductionmentioning
confidence: 99%